Insider trading networks in Brazil - Astorino, Eduardo Sanchez (2017)
The presence of insider trading in a financial market is detrimental to its functioning. Traders with public information are always at a disadvantage when negotiating with agents in possession of inside information. Thus insider trading should increase risk and should lower participation in financial markets. In this study we investigate a channel through which inside information may be transferred to market participants: social connections based on common education. We hand-collect a novel data set of the educational background of members of the board of directors of Brazilian firms and portfolio managers of stock funds. Board members hold inside information on their firms that is valuable to fund managers. We propose that these agents may engage in active social interactions if they 1) attended the same educational institution, 2) within an overlapping time window, and 3) obtained the same degree. We study if such connections influence fund managers\' portfolio decisions. We find that fund managers tend to place larger bets in companies with which they possess this sort of educational connection. We also find that these connections are economically valuable: managers tend to conduct large purchases of connected stocks prior to large increases in their return, and also tend to sell them prior to downfalls. Finally, we study if market participants view increases in a company\'s connectivity as an increase in its risk. We find that increases in connectivity are followed by increases in expected returns. We also determine that the return of holding a portfolio long in highly connected stocks and short on stocks with few connections cannot be explained by the traditional risk factors. These two results indicate that the market does indeed see connectivity as a form of risk. This is, to our knowledge, the first study of its kind for Brazil.